Therapeutic Cultural Routines to Build Family Relationships Talk, Touch & Listen While Combing Hair© - Lewis, Marva L.; Weatherston, Deborah J. (Springer International Publishing : Imprint: Springer, 2021)
XXXV, 267 p. 32 illus., 24 illus. in color.